INTEGRATIVE PROCESSES IN THE AGRICULTURAL COMPLEX OF THE NATIONAL ECONOMY - GAVKALOVA, Nataliya; DENYSIUК, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the article, the study of the essence of agro-industrial integration was further developed. It is well-founded that the creation of integrated agricultural formations contributes to the achievement of a synergistic effect, however, excessive integration has negative socio-economic consequences: monopolization of the agricultural market, making it impossible to form competitive advantages of small commodity producers, reducing the need for labor, and therefore the threat of unemployment in the countryside, which emphasizes the need for anti-monopoly control and regulation of the economy by the state, as well as support for alternative forms of combining the efforts of agricultural producers, in particular, agricultural service cooperatives. The question of the formation of product sub-complexes within the agro-industrial complex was studied. The peculiarities of inter-branch integrated structures and components of the agrarian-industrial production cycle are considered. The positive consequences of the functioning of product verticals are highlighted. Scientific views on the role of the agrarian sphere in the economy through the prism of trends in the development of the world economy are determined. It is well-founded that the main criterion for determining the role of agro-industrial complex in the economy of rural areas is the employment level of the population. The role of the agricultural sector in the regions of Ukraine is analyzed based on the employment criterion. A mechanism for the development of the agro-industrial sector as the basis of the economy of rural areas is proposed, the implementation of which is based on integration, investment and innovation directions. It is substantiated that despite the diversification processes of the economy of these territorial entities, most of them have agro-industrial specialization, so their development depends on the changes taking place in the agricultural sector. But the inconsistency of the impact of European integration on the development of the agrarian sector causes an equally contradictory situation in the socio-economic development of rural areas, as it involves the uncertainty of external conditions for their functioning and the strengthening of interregional competition. All this requires a new theoretical assessment of the peculiarities of the functioning of the agricultural sector as the basis for the development of the economy of rural areas in the context of European integration processes.
Keywords: agriculture; market; potential; state regulation; rural development; profitability; management; integration processes